2016
DOI: 10.2174/1871526516666160407113848
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Multidrug Efflux Pumps of the Major Facilitator Superfamily as Targets for Modulation

Abstract: Causative agents of infectious disease that are multidrug resistant bacterial pathogens represent a serious public health concern due to the increasingly difficult nature of achieving efficacious clinical treatments. Of the various acquired and intrinsic antimicrobial agent resistance determinants, integral-membrane multidrug efflux pumps of the major facilitator superfamily constitute a major mechanism of bacterial resistance. The major facilitator superfamily (MFS) encompasses thousands of known related seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 0 publications
1
42
0
Order By: Relevance
“…CAM chloramphenicol, ERY erythromycin, TET tetracycline, KAN kanamycin, LZD linezolid, VAN vancomycin that have been compromised by multidrug drug efflux pumps of the MFS, especially those pumps of V. cholerae (Kumar et al 2013aVarela et al 2013). Inhibitors of multidrug efflux pumps of the MFS have been extensively studied, and in many cases, however, the inhibitors are toxic to the host (Bhardwaj and Mohanty 2012;Kumar et al 2016). Thus, it is important to examine the utility of relatively non-toxic inhibitors of multidrug efflux pumps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAM chloramphenicol, ERY erythromycin, TET tetracycline, KAN kanamycin, LZD linezolid, VAN vancomycin that have been compromised by multidrug drug efflux pumps of the MFS, especially those pumps of V. cholerae (Kumar et al 2013aVarela et al 2013). Inhibitors of multidrug efflux pumps of the MFS have been extensively studied, and in many cases, however, the inhibitors are toxic to the host (Bhardwaj and Mohanty 2012;Kumar et al 2016). Thus, it is important to examine the utility of relatively non-toxic inhibitors of multidrug efflux pumps.…”
Section: Discussionmentioning
confidence: 99%
“…Efflux pumps belonging to the MFS are a large and important group of antimicrobial resistance determinants (Paulsen et al 1996;Saidijam et al 2006). Efflux pump inhibitors have been studied for the EmrB (Barrero et al 2014), LmrP (Putman et al 1999, QacA (Dymek et al 2012), and the NorA (Schindler et al 2013) multidrug efflux pumps of the MFS superfamily, summarized recently (Andersen et al 2015;Kumar et al 2016;Mukherjee et al 2016). Due to their ubiquity in bacterial pathogens and their inherent nature to circumvent infectious disease therapies, multidrug efflux pumps of the MFS are postulated to be suitable targets for modulation (Kumar et al 2013aMukherjee et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The discordance between the increase in btmD expression and the lack of change in bottromycin production in the WT + L strain (Figure 2A) led us to postulate that the potential increase in available BtmD might not be effectively channeled by the pathway and exported out of the cell, leading to increased degradation of pathway intermediates and generation of shunt metabolites. Supporting this hypothesis, previous work showed that overexpression of botT, the major facilitator superfamily (MFS) transporter gene (Kumar et al, 2016;Quistgaard et al, 2016) in the bottromycin cluster from Streptomyces sp. BC16019 increased bottromycin production in a heterologous host, although it still did not reach wild type production levels (Huo et al, 2012).…”
Section: Overexpression Of Exporter Btma Has a Moderate Positive Effementioning
confidence: 89%
“…Most of these proteins are 500 residue long single polypeptide chains with 12 to 14 transmembrane segments (TMS). The MFS group includes most of the known secondary transporters, such as transporters implicated in many human pathologies, in resistance to chemotherapeutic agents in humans and in resistance to antibiotics in bacteria (reviewed in [224,225]). Direct interactions between PE and the charge networks stabilize the inward-facing conformation, facilitating substrate release into the cytosol.…”
Section: Protein-lipid Interactions In Infectious Diseasesmentioning
confidence: 99%